In Vitro Evaluation of Adsorption Properties of Various Devices for Selective Lipopolysaccharide Hemoperfusion (Experimental Study) - A. V. Marukhov; M. V. Zakharov; N. V. Chubchenko; S. G. Shcherbak (Вестник анестезиологии и реаниматологии, 2022)
The objective: to study in vitro adsorption properties of various devices for selective lipopolysaccharide (LPS) adsorption.Subjects and Methods: Various methods of closed circuit circulating bovine serum endotoxin solutions were used. The serum was perfused using an LPS sorption device for 240 min. Serum samples were collected before the start of perfusion, and 30, 60, 120, 150, and 240 minutes after the start of circulation. LPS concentrations were measured by the turbidimetric method. One column for polymyxin hemoperfusion and three devices for selective adsorption of lipopolysaccharides were assessed.Results: When using the device for polymyxin hemoperfusion, the concentration of endotoxin in bovine serum decreased by 61% during 120 minutes, and in 120 minutes after additional administration of endotoxin, it went down by 57%. When using the other three devices, these parameters made 9% and 6%, 10% and 8%, 5% and 10%, respectively. Conclusion. By definition, an in vitro study cannot provide for complex pathophysiological reactions occurring in the body during sepsis. Тhis fact leads to limitations in extrapolating the results obtained to clinical practice.